Physico-chemical characteristics of potable water of different sources in District Nowshera: A case study after flood – 2010 - Yousaf, Saeeda; Zada, Amir; Awais, Mohammad (Journal of Himalayan Earth Sciences, 2013)
Chemical characteristics of different sources of drinking water were studied in district Nowshera, Khyber Pakhtunkhwa to know the effects of 2010 flood on drinking water. Samples of water were collected from different sources like tube wells, dug wells, and hands pump. The physical parameters including color, odour, taste, turbidity, conductivity and pH were studied whereas the chemical parameters such as total solids, total dissolved solids, total suspended, total hardness, calcium hardness, magnesium hardness, alkalinity, chlorides, sulphates, nitrites, sodium and potassium were also carried out. Most of the parameters like sulphate, nitrite, sodium contents, total solids, total dissolved solids, total suspended solids, total hardness, calcium hardness and magnesium hardness were found much higher than the permissible limits set by WHO and more than 60% of samples were found unfit for drinking purpose. It was indicated that the water quality of district Nowshera has been badly deteriorated and contaminated as a result of the flood of 2010.